Purification and Partial Characterization of Relaxin and Relaxin Precursors from the Hamster Placenta - RENEGAR, R.H. (1993)
Previous immunological studies have indicated that the molecular structure of hamster relaxin is quite different from that of porcine relaxin. In the present study, hamster relaxin was purified from placentas and characterized in order to investigate its biochemical properties. Placentas from Days 14 and 15 of gestation were homogenized in 0.26 N HCl-62.5% acetone containing protease inhibitors. After centrifugation, soluble proteins were acetone precipitated. Soluble proteins were applied to a carboxymethyl cellulose ion-exchange column and bound proteins were eluted with 0.1 and 0.3 M NaCl. Western blot analysis detected 16.5-, 18.7-, and 36.0-kDa relaxin-immunoreactive (IR) proteins within the 0.1 M NaCl eluant and detected a 5.6-kDa relaxin-IR protein within the 0.3 M NaCl eluant. The 5.6-kDa protein was purified to homogeneity by gel filtration (Sephadex G-50), ion-exchange HPLC, and C(18) -HPLC. Reduction of the 5.6-kDa protein prior to electrophoresis resulted in a single band of lower molecular mass, suggesting that hamster relaxin consists of two chains of approximately equal molecular mass. Isoelectric point of the 5.6-kDa protein was 7.78. The 16.5- and 18.7-kDa IR proteins were copurified by gel filtration and ion-exchange HPLC. At least five isoelectric point variants were observed for the 16.5- and 18.7-kDa proteins. The N-terminal amino acid for the 5.6 and 18.7 relaxin-IR proteins was arginine, and subsequent cycles indicated an identical partial sequence that was consistent with that for relaxins from other species.